Solve all your doubts with Teachoo Black (new monthly pack available now!)

Are you in **school**? Do you **love Teachoo?**

We would love to talk to you! Please fill this form so that we can contact you

Examples

Example 1

Example 2

Example 3

Example 4

Example 5 Important

Example 6

Example 7 Important

Example 8

Example 9 Important

Example 10

Example 11 Important

Example 12 Important

Example 13 Important

Example 14 Important

Example 15 Important

Example 16

Example 17 Important

Example 18 Important

Example 19 Important

Example 20 Important

Example 21 Important

Example 22

Example 23

Example 24 Important

Example 25 Important

Example 26 Important

Example 27

Example 28 Important Deleted for CBSE Board 2023 Exams

Example 29 Important

Example 30 Important Deleted for CBSE Board 2023 Exams

Example 31 Important Deleted for CBSE Board 2023 Exams

Example 32 Important Deleted for CBSE Board 2023 Exams

Example 33 Important

Example 34 Deleted for CBSE Board 2023 Exams

Example 35

Example 36 Important You are here

Example 37 Important

Chapter 13 Class 12 Probability

Serial order wise

Last updated at Feb. 15, 2020 by Teachoo

Example 36 A and B throw a die alternatively till one of them gets a ‘6’ and wins the game. Find their respective probabilities of winning, if A starts first. Winning the game is getting a 6 on the die P(getting 6) = 1/6 P(not getting six) = 1 – P(getting six) = 1 – 1/6 = 5/6 1st throw by A: A gets a six P(A wins) = 1/6 2nd throw by B: A does not get 6, B gets six So, P(B wins) = 5/6 × 1/6 3rd throw by A: A does not get 6, B does not get 6, A gets six P(A wins) = 5/6 × 5/6 × 1/6 4th throw by B: A does not get 6, B does not get 6, A does not get 6, B gets six P(B wins) = 5/6 × 5/6 × 5/6 × 1/6 5th throw by A: A does not get 6, B does not get 6, A does not get 6, B does not get 6, A gets six P(A wins) = 5/6 × 5/6 × 5/6 × 5/6 × 1/6 and so on So, probability that A wins is P(A wins) = 1/6 + 5/6 × 5/6 × 1/6 + 5/6 × 5/6 × 5/6 × 5/6 × 1/6 + ……. = (1/6) + (5/6)^2 (1/6) + (5/6)^4 (1/6) + ............ Sum of infinite GP : a, ar , ar2, …….. a + ar + ar2 + ……… = 𝑎/(1 − 𝑟) Here, a = 1/6 , r = (5/6)^2 = (1/6)/(1 − (5/6)^2 ) = (1/6)/(1 − 25/36) = (1/6)/((36 − 25)/36) = (1/6)/(11/36) = 6/11 ∴ P(A wins) = 𝟔/𝟏𝟏 and P(B wins) = 1 – P(A wins) = 1 – 6/11 = 𝟓/𝟏𝟏